2012
DOI: 10.1007/s10143-012-0424-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between elevated plasma norepinephrine levels and cardiac wall motion abnormality in poor-grade subarachnoid hemorrhage patients

Abstract: Patients with aneurysmal subarachnoid hemorrhage (SAH) are frequently complicated by acute cardiac dysfunctions, including cardiac wall motion abnormality (WMA). Massive release of catecholamine into the systemic circulation after aneurysmal rupture is believed to result in WMA, and poor-grade SAH seems to be the most important risk factor. However, plasma catecholamine levels have rarely been measured in SAH patients with WMA, and previous studies indicated that the elevated levels might not necessarily predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…In that preclinical study, catecholamine release lasted less than 2 hours and was followed by a sustained increase in biological markers of cardiac injury and alterations of myocardial function [14]. Our study shows that as reported in the literature [15,27], there is already marked and rapid catecholamine release at admission. The source of SAH-induced catecholamine release remains unknown.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In that preclinical study, catecholamine release lasted less than 2 hours and was followed by a sustained increase in biological markers of cardiac injury and alterations of myocardial function [14]. Our study shows that as reported in the literature [15,27], there is already marked and rapid catecholamine release at admission. The source of SAH-induced catecholamine release remains unknown.…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that the pathophysiology of cardiac injury after SAH is similar to apical ballooning syndrome (Takotsubo or stress cardiomyopathy) that is, in relation to catecholamine endogenous release [14]. Few human studies have shown an association between catecholamine release and cardiac dysfunction at an early stage after SAH, and to our knowledge few human studies have focused on the time course of catecholamine release and cardiac dysfunction during SAH [5,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Activation of the sympathetic nervous system, which leads to an elevated level of circulating, cerebrospinal fluid (CSF), and urine catecholamines, may be the link between the initial ictus and the genesis of some of the systemic complications after SAH [13]. Sympathetic activation was observed as an elevation of plasma norepinephrine following preclinical and clinical SAH studies [14, 15]. It has been well recognized that a high sympathetic tone combined with high circulating catecholamine concentrations may occur in humans with head injury, particularly after SAH [13, 16].…”
Section: Possible Mechanisms Of Nonneurologic Complications Followmentioning
confidence: 99%
“…In contrast, published data for spontaneous subarachnoid haemorrhage suggests large increases in plasma NE with minor or no elevation of E levels. (38)(39)(40)(41)(42) The increase in E suggests a possible causative role from the motor overactivity that is part of the syndrome in PSH but not SAH. Whatever the cause, the difference in catecholamine response seen in these two conditions suggests that their underlying pathophysiology are not equivalent.…”
Section: Discussionmentioning
confidence: 95%